Model Otonomi Daerah di Denmark dan Zimbabwe serta Alternatif Model Pengawasan Otonomi Daerah di Indonesia - Prabowo, Hadi (Research and Development Agency Ministry of Home Affairs, 2020)
Law No. 12 of 2017 concerning the Guidance and Oversight of the Administration of Regional Governments apparently has not provided sufficient power for the implementation of regional autonomy in Indonesia. In fact, a number of cases that undermine the implementation of regional autonomy still occur frequently. There are many contributing factors, including the current regional autonomy oversight system. The Regional Autonomy Implementation Monitoring Committee (KPPOD), for example, noted implementing regulations related to sanctions for regional governments that commit violations or disobey, such as delays in preparing regional budgets, negligence in national programs, or noticeless overseas travels, were not firm yet. On the other hand, guidance and oversight were still considered weak. Therefore, this study intended to provide an overview of regional autonomy oversight models in Denmark and Zimbabwe while trying to provide a solution for the regional autonomy oversight model in Indonesia. To achieve this goal, this study used a literature study method to gather various relevant information with a qualitative approach. This approach was considered appropriate because regional autonomy oversight was multidimensional. The results showed that such a regional autonomy oversight model as applied in Denmark was needed to control regional governments from implementing policies that could harm public interest. Furthermore, the oversight must be carried out by looking at the problems and the actual conditions in the regions in more detail. This study also offered a regional autonomy oversight model, which has dimensions of human resources, acceptance, development, and innovation.